Dynamics of dissolved Fe content in tributaries of Lake Teletskoe, depending on solar activity indicators - Alexander V. Puzanov; Svetlana V. Baboshkina; Tamara A. Rozhdestvenskaya; Sergey N. Balykin; Dmitry N. Balykin; Alexey V. Saltykov; Irina A. Troshkova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Relevance. The need to expand and deepen the understanding of the influence of solar radiation indicators on chemical characteristics of surface water, since the dependence of hydrochemical processes on periodic changes in solar activity has so far been studied extremely poorly. In addition, special attention is paid worldwide to the study of iron content in waters of rivers and lakes. Iron increased concentrations are one of the reasons for the "brownification" of surface waters in a significant part of the Northern Hemisphere. Aim. To establish a relationship between iron content and dynamics in the waters of the tributaries of Lake Teletskoe with indicators of solar activity (sunspots number, F-index). Methods. Water samples from the tributaries of Lake Teletskoe were collected into clean new polyethylene bottles in the estuaries of the rivers, from a depth of 0.5 m during the spring-summer high water and autumn low water, in 2016–2020. Content of total and dissolved Fe in the waters was determined by the ISP-MS method and by the AAS method. We used the data on solar activity indicators from the Belgian Observatory, which are freely available. Results. The total Fe content in the rivers of Lake Teletskoe basin for the period from 2016 to 2020 changes from 5 to 340 µg/l. Concentrations of dissolved iron (4 to 200 µg/l) do not exceed Russian standards, but they are often noticeably higher than the global average for river waters established abroad. The highest iron content, as well as the proportion of its soluble forms in the tributaries of Lake Teletskoe and in lake waters, was noted in 2016. It is probably due to the highest rates of solar activity. They cause certain changes in the environment – such as an increase in air temperature and water evaporation, and decrease in river flow, which accompanied by growth in concentrations of chemical elements in surface waters. Since 2016, there has been a steady decrease in dissolved iron concentration in surface natural waters of Lake Teletskoe basin, which may be a consequence of a decrease in solar radiation intensity in recent years.